How animals care for their babies : kids want to know - Hirschland, Roger B. (Washington, D.C : National Geographic Society, 1989)
Depicts different kinds of parental behavior among a variety of animals, including the trumpeter swan, mountain goat, and baboon.
Includes bibliographical references
Keywords: Parental behavior in animals-Juvenile litearture; Animals-Infancy-Juvneile literature; National Geographic Society (U.S.)